KONSTRUKSI SOSIAL PEREMPUAN NELAYAN DALAM POLA DAN RELASI SOSIOKULTURAL DI KAWASAN PESISIR PANTAI KARANGANTU SERANG BANTEN - Indrianti Azhar Firdausi; Ahmad Sururi; Abdul Malik (Titian: Jurnal Ilmu Humaniora, 2021)
The phenomenon of the status, position and role of fisherwomen are still objects and minorities in the household with an unequal division of labor, tend to be subordinates, marginalized social status, lack of access to decision-making processes and as well as gender socio-cultural barriers in carrying out various activities in the public sphere. problems in this research. The purpose of this study is to discuss how the sociocultural patterns and relations of women fishermen in the Karangantu Coastal Area, Serang Banten and the efforts made to encourage the strengthening of women's roles in sociocultural relations that can be accepted and agreed upon in social communication. This research method uses a social construction approach through 3 stages, namely: externalization, internalization and objectivation. Data collection techniques were carried out through interviews and in-depth observations. The results show that the social construction of fisherwomen in the process of social action and interaction in the public sphere is limited by a patriarchal cultural tradition that is strongly formed and internalized in the form of adherence to norms, values, patterns and cultural relations. The implication of this research is to encourage the strengthening of women's roles within boundaries that can be constructed socially and culturally as well as through equality of social communication.